Selective Restoration of Pomc Expression in Glutamatergic POMC Neurons: Evidence for a Dynamic Hypothalamic Neurotransmitter Network - Jones, Graham L. (eNeuro, 2019)
Hypothalamic POMC deficiency leads to obesity and metabolic deficiencies, largely due to the loss of melanocortin peptides. However, POMC neurons in the arcuate nucleus (ARC) are comprised of glutamatergic and GABAergic subpopulations. The developmental program, relative proportion and function of these two subpopulations are unresolved. To test whether glutamatergic POMC neurons serve a distinct role in maintaining energy homeostasis, we activated Pomc expression Cre- dependently in Vglut2-expressing neurons of mice with conditionally silenced Pomc alleles. The Vglut2-Pomc restored mice had normal ARC Pomc mRNA levels, POMC immunoreactivity, as well as body weight and body composition at age 12 weeks. Unexpectedly, the cumulative total of Vglut2(+) glutamatergic- and Gad67(+) GABAergic-Pomc neurons detected by in situ hybridization (ISH) exceeded 100% in both Vglut2- Pomc restored and control mice, indicating that a subpopulation of Pomc neurons must express both neuronal markers. Consistent with this hypothesis, triple ISH of C57BL/6J hypothalami revealed that 35% of ARC Pomc neurons were selectively Gad67 (+), 21% were selectively Vglut2 (+), and 38% expressed both Gad67 and Vglut2. The single Gad67 (+) and Vglut2 (+) Pomc neurons were most prevalent in the rostral ARC, while the Vglut2/Gad67 (+) dual-phenotype cells predominated in the caudal ARC. A lineage trace using Ai9-tdTomato reporter mice to label fluorescently all Vglut2-expressing neurons showed equal numbers of tdTomato(+) and tdTomato(-) POMC immunoreactive neurons. Together, these data suggest that POMC neurons exhibit developmental plasticity in their expression of glutamatergic and GABAergic markers, enabling re-establishment of normal energy homeostasis in the Vglut2-Pomc restored mice.